Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Di Dinas Pendidikan Dan Kebudayaan Kabupaten Bulukumba - Ahmad, Andi Jusdiana; Mappamiring, Mappamiring; Mustari, Nuryanti (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study aimed to analyze the effect of the work environment on employee performance at the Education and Culture Office of Bulukumba Regency. The type of research used in this study was a mix method (quantitative and qualitative) with data collection techniques used namely observation, questionnaires, interviews, and documentation. As for the number of samples used in this study as many as 55 people and 9 informants. The data were analyzed using simple linear regression analysis. The results showed that the influence of the work environment on the performance of employees at the Education and Culture Office of Bulukumba Regency went well. This was based on the average score obtained from the statement items of 77.97% which indicated that the work environment occupies a good category. Then the research also showed that the work environment had a positive and significant effect on the performance of employees at the Education and Culture Office of Bulukumba Regency by 53.6% and the rest, which was 46.4%, the performance of employees was influenced by other factors.Keywords: Work environment, Employee performance.